Electroless nano zinc oxide-activate carbon composite supercapacitor electrode - Faraji, Soheila (Springer, 2016)
An electroless deposition process was used to synthesize the nanostructured zinc oxide (ZnO)-activated carbon (AC) as supercapacitor. The composite oxide was studied by high resolution transmission electron microscopy (HRTEM), scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction analysis (XRD). The electrochemical performance of the nanocomposite was analyzed through cyclic voltammetry (CV) and AC impedance spectroscopy (EIS) in 0.1 M Na2SO4 as electrolyte. A specific capacitance 187 F g(-1) at a scan rate of 5 mV s(-1) was obtained using cyclic voltammetry (CV) and a nearly rectangular shaped CV curve was observed for the composite oxide. The supercapacitor was quite stable during charge-discharge cycling and exhibited constant capacitance during the long-term cycling. It also yielded a specific capacitance 171 F g(-1) at 5 mA cm(-2) with a high energy density of 21.9 Wh kg(-1) and 4.2 kW kg(-1) of power density. Due to unique structure of prepared ZnO-AC nanocomposite, it is a promising candidate for supercapacitor.